Contemporary Arabic Idiomatic Expressions and Methods of Teaching l Al-Ta’birat al-Ishthilahiyyah al-‘Arabiyyah al-Mu‘asharah wa Thara’iqu Ta’limiha - Wardhana, Delly; Bahruddin, Uril; Mahmoud Alzitawi, Diaya Uddeen Deab (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2023)
This study started from the problem of the difficulty of teaching modern Arabic idioms among students of Babussalam As-Sunnah Institute in Depok. Although proficiency in it is an important part and it has a big role when acquiring the Arabic language fully and completely. This study aimed to reveal the difficulties of the Arabic teaching as well as to clarify the proposed teaching methods for the teaching. This research used a qualitative and descriptive approach, which is an analysis used to collect metadata. This research was conducted at the Babussalam Islamic Boarding School an Educational Institution under the auspices of the Babussalam As-Sunnah Foundation, Cimanggis, Depok, West Java. The results of this study found that difficulties from the point of view of Arabic teachers involved in the study procced from the following main aspects: the educational environment, educational curriculum or in its broadest sense, learners and teachers. The result of the research indicated the proposed teaching methods for teaching modern Arabic idioms from the book, there are: the inductive method, standard method, informative or repeating or speech method and dialogue method.